Matriarchal Exemplarity in Elizabeth Isham’s Booke of Rememberance - Emma Rayner (Sillages Critiques)
Elizabeth Isham’s Booke of Rememberance (written 1638-9) has emerged in recent decades as one of the seventeenth century’s finest surviving examples of life-writing. Scholars have pointed, in particular, to Isham’s achievement in fashioning a fairly coherent self despite the generic hybridity of her manuscript diary. A principal source of that hybridity is the advice and templates for conduct that Isham “calls to mind” from her mother, grandmother, and sister – familial inheritances that gain posthumous currency as her life narrative progresses, and the cycles of illness and death it traces subsume these female relatives one by one. This article focuses on the ways in which Isham absorbs matriarchal example into her narrative by examining the Booke’s treatment of Lady Judith Isham’s spiritual melancholy. The exemplary rhetoric employed by Isham around her mother’s illness proves that it is not despite but because of the generic hybridity of her diary that a coherent strain emerges within it – if not in the form of a recognizable modern “self,” then in the shape of multiple lives bound into one multi-generational matriarchal consciousness.